Dynamics and chronology of Mycoplasma hyopneumoniae strain 232 infection in experimentally inoculated swine - Almeida, Henrique M. S. (Porcine Health Manag, 2021)
Direct detection of Mycoplasma hyopneumoniae through molecular tools is a growing trend for early diagnosis, highlighting the importance of knowing M. hyopneumoniae dynamics in the respiratory tract upon infection. This study focused on monitoring the infection level and its effects in different anatomic sites of the respiratory tract of experimentally infected swine in four time-points post-infection. To this end, 24 pigs were allocated to either non-inoculated group (n = 8) or inoculated group (n = 16). On day 0 post-infection (dpi), animals of the inoculated group were intratracheally inoculated with M. hyopneumoniae. Nasal swabs were collected weekly for qPCR detection of bacterial shedding. At 14, 28, 42, and 56 dpi, four animals from the inoculated group and two from the control group were necropsied. Bronchoalveolar lavage fluid (BALF) and samples from three different anatomical tracheal sections (cranial - CT, medium - MT, lower - LT) were collected for qPCR and histopathology. Bacterial loads (qPCR) in tracheal samples were: 4.47 × 10(2) copies∕μL (CT), 1.5 × 10(4)- copies∕ μL (MT) and 1.4 × 10(4) copies∕μL (LT samples). M. hyopneumoniae quantification in BALF showed the highest load at 28 dpi (2.0 × 10(6) copies∕ μL). Microscopic lesions in LT samples presented the highest scores at 56 dpi and were significantly correlated with the pathogen load on 14 dpi (0.93) and 28 dpi (0.75). The greatest bacterial load of M. hyopneumoniae in CT samples and BALF was registered at 28 dpi, and it remained high in BALF and LT throughout the 56 dpi. The pathogen was able to persist during the whole experimental period, however higher estimated quantification values were registered in the lower parts of the respiratory tract, especially at 56 dpi. These findings are important for improving diagnostics, treatment, and control measures of M. hyopneumoniae infection in swine herds.